2020
DOI: 10.1159/000510441
|View full text |Cite
|
Sign up to set email alerts
|

Usual-Type Endocervical Adenocarcinoma with a Microcystic, Elongated, and Fragmented Pattern of Stromal Invasion: A Case Report with Emphasis on Ki-67 Immunostaining and Targeted Sequencing Results

Abstract: The microcystic, elongated, and fragmented (MELF) pattern is a unique myometrial invasion pattern occasionally found at the invasive front of endometrial endometrioid carcinoma (EEC). Herein, we report an uncommon case of usual-type endocervical adenocarcinoma (UEA) with a MELF pattern. We comprehensively analyzed its clinicopathological and molecular features, which has not been previously documented. A 67-year-old woman presented with a cervical mass and underwent radical hysterectomy. Histologically, the ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The latter manifests as variable-sized morules or solid sheets of eosinophilic cells with occasional keratinization, whereas the former is characterized by the presence of columnar or pseudostratified epithelial cells containing intracytoplasmic mucin. Three (6.0%) patients developed tumors that showed a microcystic, elongated, and fragmented pattern of myometrial invasion, which is characterized by loss of conventional glandular architecture, presence of squamoid or histiocyte-like cells with eosinophilic cytoplasm, formation of microcysts, compressed elongated structures, flattened and fragmented glandular epithelium, and an edematous or fibromyxoid stroma associated with an acute inflammatory response 25–29 .…”
Section: Resultsmentioning
confidence: 99%
“…The latter manifests as variable-sized morules or solid sheets of eosinophilic cells with occasional keratinization, whereas the former is characterized by the presence of columnar or pseudostratified epithelial cells containing intracytoplasmic mucin. Three (6.0%) patients developed tumors that showed a microcystic, elongated, and fragmented pattern of myometrial invasion, which is characterized by loss of conventional glandular architecture, presence of squamoid or histiocyte-like cells with eosinophilic cytoplasm, formation of microcysts, compressed elongated structures, flattened and fragmented glandular epithelium, and an edematous or fibromyxoid stroma associated with an acute inflammatory response 25–29 .…”
Section: Resultsmentioning
confidence: 99%
“…They speculated that on the invasive tumor front, the elevated expression of NNMT might contribute to the characteristic morphology of MELF through the suppression of H3K9me2 followed by the enhancement of various pathways related to cell migration and invasion [37]. Meanwhile, the molecular features of MELF pattern in EAC have only been investigated in our recent case study [15]. In this single-case report, we conducted targeted sequencing analysis using tissue samples obtained from the MELF and conventional tumor areas of usual-type HPVA EAC.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported in EEC that the tumor cells and glands representing MELF pattern are rarely positive for Ki-67, suggesting that MELF pattern is associated with cellular senescence or growth arrest [8,15,34]. Kihara et al [8] suggested that these findings can explain why there is no significant difference in patient survival between MELF-positive and MELF-negative groups, despite more frequent LVSI and LNM in patients with EEC with MELF pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation